Experimental Study of the Creep Disturbance Effect and Acoustic Emission Characteristics of Mudstone with Different Moisture Contents - Yongjiang Yu; Pengbo Wang; Shipeng Zhang; Jingjing Liu (Shock and Vibration)
It is important to have a clear understanding of the creep characteristics of water-rich soft rocks under a dynamic load and the evolution of cracks because soft rock roadways in deep mines are very sensitive to disturbances, and instability and damage can easily occur under the impact of disturbances such as mining and blasting. In this study, a self-developed disturbed creep test bench was used to conduct graded loading creep disturbance tests on mudstone specimens with different moisture contents. The results show that an increase in the moisture content leads to a significant increase in the creep failure strain of mudstone, and the accelerated creep rate is greatly accelerated. Moreover, as the moisture content increases, the type of mudstone creep disturbance failure gradually changes from accelerated creep failure to disturbance failure. By analyzing the acoustic emission (AE) characteristics of the mudstone creep disturbance tests, it was found that the increase in the moisture content greatly weakens the AE count and the accumulated energy. In each stage of disturbance, the AE signals jumped, and the stability was restored at the end of the disturbance. As the load increased, the specimen entered the accelerated creep stage, the AE signal increased exponentially, and the internal cracks expanded rapidly until failure occurred. It is of great significance to carry out creep disturbance experiments and to analyze the evolution of the internal cracks in specimens with different moisture contents to maintain the long-term stability of deep soft rocks.